2013
DOI: 10.1007/s11010-013-1659-x
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effect of quercetin in ectoenzymes and acetylcholinesterase activities in cerebral cortex synaptosomes of cadmium-exposed rats

Abstract: This study investigated the effect of quercetin on nucleoside triphosphate diphosphohydrolase (NTP-Dase), 50-nucleotidase, adenosine deaminase (ADA), and acetylcholinesterase (AChE) activities in synaptosomes from cerebral cortex of adult rats exposed to cadmium (Cd). Rats were exposed to Cd (2.5 mg/Kg) and quercetin (5, 25 or 50 mg/Kg) by gavage for 45 days. Rats were randomly divided into eight groups (n = 8-10): saline/ethanol, saline/Querc 5 mg/kg, saline/Querc 25 mg/kg, saline/Querc 50 mg/kg, Cd/ethanol, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 63 publications
3
24
0
Order By: Relevance
“…However, the specific intervention mechanism needs further study. Treatment with quercetin (5, 25, or 50 mg/kg) and Cd (2.5 mg/kg) reduced NTPDase, 5′‐nucleotidase, ADA, and AChE activity in synaptosomes from the cerebral cortex of adult rats exposed to Cd . However, quercetin totally or partially prevented oxidative stress and increased AChE and Na + ,K + ‐ATPase activities in the cerebral cortex, hippocampus, and hypothalamus of rats exposed to Cd, preventing memory impairment and anxiogenic‐like behavior (Fig.…”
Section: Nutritional Intervention For Osteoporosismentioning
confidence: 97%
See 3 more Smart Citations
“…However, the specific intervention mechanism needs further study. Treatment with quercetin (5, 25, or 50 mg/kg) and Cd (2.5 mg/kg) reduced NTPDase, 5′‐nucleotidase, ADA, and AChE activity in synaptosomes from the cerebral cortex of adult rats exposed to Cd . However, quercetin totally or partially prevented oxidative stress and increased AChE and Na + ,K + ‐ATPase activities in the cerebral cortex, hippocampus, and hypothalamus of rats exposed to Cd, preventing memory impairment and anxiogenic‐like behavior (Fig.…”
Section: Nutritional Intervention For Osteoporosismentioning
confidence: 97%
“…found that Cd‐impaired memory and neurological disorders were associated with decreased activity of AChE and the Na + ,K + ‐ATPase in the cerebral cortex and the hippocampus of Cd‐exposed rats. AChE activity increased in synaptosomes from the cerebral cortex of adult rats exposed to Cd . ATP or ADP can be hydrolyzed by nucleoside triphosphate diphosphohydrolase (NTPDase) to form Aronia melanocarpa berry (AMP), as its hydrolysis contributes to adenosine formation in the presence of 5′‐nucleotidase.…”
Section: Cd‐induced Toxicitymentioning
confidence: 99%
See 2 more Smart Citations
“…The hydrolytic enzyme, cholinesterase, regulates ACh levels by breaking down this neurotransmitter in many tissues. AChE activity is altered in response to redox imbalance and affected by various degree of injury to the organism which can stimulate rapid ACh degradation and consequently, decreased stimulation of ACh receptors leading to negative effects on cholinergic neurotransmission as well promotion of cognitive impairment (Elufioye et al, 2010;Abdalla et al, 2013 The neurotransmitter, dopamine, is produced from the amino acid, tyrosine, through the catalytic action of tyrosine hydroxlase (TH) which is the rate-limiting enzyme in the pathway. (Daubner and Wang, 2011).…”
Section: Discussionmentioning
confidence: 99%